Answer:
![f^-^1(x)=((x+1)^2)/(16)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/w94asoiibdbrgteyg9vp8sk7sal33rlt1i.png)
Explanation:
We have the function:
and we have to find the inverse.
Observation:
, then
![y=-4√(x) -1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/zcinz3g7jzc8i3rymv2vkcavru2fx0xelc.png)
You can obtain the inverse of a function by switching the x and y values. This means:
![y=-4√(x) -1\\x=-4√(y') -1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/bsqn42k9i7593x3euurdo7ro607d9oip7z.png)
We're going to call
. Now we have to clear "y'".
First we have to add (1) in both sides of the equation:
![x=-4√(y') -1\\x+1=-4√(y')-1+1\\x+1=-4√(y')](https://img.qammunity.org/2019/formulas/mathematics/middle-school/soq9c2j0vk2kz1gzpr94p6j7g1bllvdxha.png)
Now divide in (-4) both sides.
![x+1=-4√(y')\\((x+1))/((-4)) =((-4)√(y'))/((-4)) \\\\((x+1))/((-4)) =√(y')](https://img.qammunity.org/2019/formulas/mathematics/middle-school/s01kbrf6u92snvjr38hgtjhfgxsb2jaoq3.png)
And for our last step we have to square both sides:
![((x+1))/((-4)) =√(y')\\\\(((x+1))/((-4)))^2=(√(y'))^2\\((x+1)^2)/((-4)^2)=y'\\\\((x+1)^2)/(16)=y'](https://img.qammunity.org/2019/formulas/mathematics/middle-school/i7ajp1rq7ilou1sh7sg77aa68bywpotoyj.png)
Then the third option is the correct:
![f^-^1(x)=((x+1)^2)/(16)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/w94asoiibdbrgteyg9vp8sk7sal33rlt1i.png)